Intergranular precipitation-enhanced wetting and phase transformation in an Al0.4CoCrFeNi high-entropy alloy exposed to lead-bismuth eutectic. (March 2022) - Gong, Xing; Auger, Thierry; Zhu, Wenjian; Lei, Huasheng; Xiang, Congying; Yu, Zhiyang; Short, Michael P.; Wang, Pei; Yin, Yuan
Abstract: After exposure to oxygen-poor (10 −13 –10 −14 wt%) liquid lead-bismuth eutectic (LBE) at 500 °C for 500 h, LBE penetrates more than one order of magnitude deeper in an FCC Al0.4 CoCrFeNi high-entropy alloy (HEA) decorated with a network of BCC (Ni, Al)-rich intergranular (IG) precipitates than in a single-phase, FCC Al0.3 CoCrFeNi HEA without the IG precipitate network. This deterioration of corrosion resistance is attributed to the energetic nature of the BCC/FCC interphase boundaries (IBs) and resultant IB wetting. The LBE ingress film selectively leaches nickel located at those low-indexed crystalline planes, resulting in phase transformation from FCC to BCC structure. Highlights: A network of precipitates at GBs enhances highly corrosion kinetics. Wetting is responsible for the fast LBE ingress at the interphase boundaries. Leaching of Ni leads to phase transformation from FCC to BCC structure.